Family language policy among upper-middle class families in Beijing / Zou Xiaoqiong - Zou, Xiaoqiong (2015)
This study focuses on a group of Chinese parents from the upper-middle class who are raising their children bilingually. It uses the lens of family language policy (FLP) to investigate the process of raising a bilingual child, how parents perceive language(s) and how their beliefs transform into actual language practices and management at home for their child’s language development. An ethnographic method is used to collect data with data sources that provide insight into actual language practices, parental language ideology and their sources, and parental language management. The findings reveal that there is a visible shift from Chinese to English that is generational among participants, all parents hold an unambiguous belief in the benefits of developing English because it provides overt socioeconomic and educational opportunities. Further, parent participants take advantage of English educational institutions (cram schools and home tutors) to implement their family language policies (FLPs) instead of speaking English themselves.